Kết quả chọn tạo một số dòng lúa nếp mới - Đào, Xuân Tân (Bộ Giáo dục và Đào tạo, 2014)
Breeding hybrids in the year of 1993. In the yth generation was selection 6 line glutinous rice (N16, N17, N20, N22, N24 ). They bring with many specific charater of the glutinous rice. The trai ts: tilering , panicle on clump, volum seed on c1um are in leven rath er and high. Line N17 have productivity - higest (8 ,27 T/ha). Hoever coefficient on variation is very higt in some lines on some charater: tilering and panicle on c1um (N14 , N20) (One of them in 6th generation wastake part in stydy on system nation al variety).